A Review on Product Development of Islamic Social Finance in Tijari Sector - Rahim, Norafni @ Farlina; Shahwan, Syahidawati; Shafii, Zurina; Mirza, Azrul Azlan Iskandar; Sapian, Safeza; Salleh, Supiah; Nawai, Norhaziah; Ibrahim, Norhazlina; Haris, Asmaddy (UUM Press, 2018)
Social finance is not new, but most low-income earners are not keen to utilize social finance products due to its association with riba (usury). Islamic social finance on the other hand offers the alternative to generate economy and create wealth, with its Shariah-compliant underlying principles. This new mechanism offers the alternative for people under the paradigm of Islamic economic system. This instrument covers the deficiency of Islamic finance, in both ijtimaie and tijari sectors. Thus, it is crucial to the stages involved in the creation of Shariah-compliant products that can meet the objectives of ijtimaie and tijari sectors. The main objective of this paper is to review the concept and paradigm of Islamic economic system and the position of Islamic social finance. It also reviews the product development and innovation of this mechanism. The methodology used for this is qualitative in nature, namely content analysis of the secondary sources of similar themes. It was found that there is very limited discussion on product development in Islamic social finance.